2015
DOI: 10.1007/s11356-015-5174-3
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of UV filters in natural and drinking water in São Paulo State (Brazil)

Abstract: Ultraviolet (UV) filters are widely used in the formulation of personal care products (PCPs) to prevent damage to the skin, lips, and hair caused by excessive UV radiation. Therefore, large amounts of these substances are released daily into the aquatic environment through either recreational activities or the release of domestic sewage. The concern regarding the presence of such substances in the environment and the exposure of aquatic organisms is based on their potential for bioaccumulation and their potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(18 citation statements)
references
References 29 publications
0
15
0
3
Order By: Relevance
“…em amostras de água tratada coletadas em cidades do interior do estado de São Paulo empregando Cromatografia Gasosa acoplada à Espectrometria de Massas sequencial (GC-MS/MS). 25 Rissato e colaboradores determinaram 6 pesticidas organoclorados (BHC, aldrim, dieldrin, DDT, endossulfan e heptaclor) em amostras de água tratada da cidade de Bauru (SP) em concentrações que variaram entre 8 e 33 ng L -1 utilizando cromatografia gasosa de alta resolução com detector de captura de elétrons (HRGC-ECD), o qual apresenta detectabilidade adequada à análise de resíduos de compostos voláteis ou semi-voláteis, como são esses analitos de interesse. 30 E, finalmente, Stumpf e colaboradores, em seu trabalho pioneiro para o Brasil, determinaram 15 DBP incluindo compostos neutros e ácidos em concentrações entre 100 e 41000 ng L -1 empregando GC-ECD, e determinou EDTA em concentrações de 2000 ng L -1 empregando cromatografia gasosa com detector de nitrogênio-fósforo (GC-NPD) em amostras de água tratada oriunda da Lagoa de Juturnaíba na Região dos Lagos (RJ).…”
Section: Contaminantes Emergentes No Brasilunclassified
“…em amostras de água tratada coletadas em cidades do interior do estado de São Paulo empregando Cromatografia Gasosa acoplada à Espectrometria de Massas sequencial (GC-MS/MS). 25 Rissato e colaboradores determinaram 6 pesticidas organoclorados (BHC, aldrim, dieldrin, DDT, endossulfan e heptaclor) em amostras de água tratada da cidade de Bauru (SP) em concentrações que variaram entre 8 e 33 ng L -1 utilizando cromatografia gasosa de alta resolução com detector de captura de elétrons (HRGC-ECD), o qual apresenta detectabilidade adequada à análise de resíduos de compostos voláteis ou semi-voláteis, como são esses analitos de interesse. 30 E, finalmente, Stumpf e colaboradores, em seu trabalho pioneiro para o Brasil, determinaram 15 DBP incluindo compostos neutros e ácidos em concentrações entre 100 e 41000 ng L -1 empregando GC-ECD, e determinou EDTA em concentrações de 2000 ng L -1 empregando cromatografia gasosa com detector de nitrogênio-fósforo (GC-NPD) em amostras de água tratada oriunda da Lagoa de Juturnaíba na Região dos Lagos (RJ).…”
Section: Contaminantes Emergentes No Brasilunclassified
“…In a study done in Morro Redondo, Brazil, 14 of the 16 ECs studied were detected in drinking water samples; one of the most concentrated compounds was atrazine (Maximum: 92.3 ngL -1 ) (Caldas et al, 2013). Another study conducted at 6 DWTPs in the state of São Paulo found 6 UV filters (da Silva et al, 2015). A national survey conducted in Brazil found 4 of the 16 ECs in drinking water; the most frequent being atrazine (Medium: 6.5 ngL -1 , Maximum: 24 ngL -1 , 75%) and caffeine (Medium: 146 ngL -1 , Maximum: 2.77 μgL -1 , 93%) (Machado et al, 2016).…”
Section: Wastewater (Wwtp) and Drinking Water Plants (Dwtp) To Eliminmentioning
confidence: 99%
“…Chemical UV filters get directly into the environment as a result of washing away from the skin, washing clothes, while practicing water sports, as well as indirectly with municipal or industrial wastewater. These compounds have been identified as impurities in wastewater (Plagellat et al 2006;Moeder et al 2010;Zhang et al 2011;Tsui et al 2014a;Ekpeghere et al 2016), lakes (Poiger et al 2004;Balmer et al 2005), and rivers (Fent et al 2010) at levels of ng L −1 and μg L −1 even in tap water (Díaz-Cruz et al 2012;da Silva et al 2015). Because they are applied as ingredients of shampoos, creams, and other personal protection products, they are found in both urban and rural wastewater and have also been identified in industrial wastewater.…”
Section: Introductionmentioning
confidence: 99%